Online EFL business writing with GenAI-generated templates: Students’ performance and perceptions - Tsai, Shu-Chiao (Australasian Journal of Educational Technology, 2025)
Generative artificial intelligence (GenAI) has been increasingly used to facilitate and evaluate EFL academic writing, but few studies have been conducted on business writing. Furthermore, little empirical research has evaluated the quality of the GenAI-generated templates. An approach using English GenAI-generated templates as feedback (GenAI-GETF) was implemented in two business contexts for 117 non-English major English as a Foreign Language (EFL) students in two groups, respectively. A pre-test and post-test design was conducted to assess students’ writing performance, and a questionnaire survey was administered to investigate their perceptions. Results indicate that the GenAI-generated templates provided more enriched and professional content than samples excerpted from textbooks. Students showed significantly better performance in the post-writing than in the pre-writing, such as writing more enriched content, using more high-order words, having a lower probability of writing errors and performing higher writing scores. They also showed high satisfaction with their learning through the GenAI-GETF approach. The use of AI-based tools combined with student-centred activities assigned in this study provided a dynamic, interactive and self-paced learning environment in which students were able to immediately receive multimodal input, scaffolding and personalised feedback to improve their content-based and linguistic knowledge of their post-writing. These findings provide practical solutions and implications for the concerns often encountered in using technology. Implications for practice or policy: The GenAI-GETF approach with a five-step learning model should be implemented in EFL business writing. EFL students should make good use of the features of GenAI and free AI-based resources to promote comprehensive input and output and obtain instant and personalised feedback for achieving improved writing performance. EFL teachers should adopt technological resources to create a flexible and interactive learning environment where students’ interaction and outcomes can be effectively enhanced.